2022
DOI: 10.3390/vaccines10030448
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 T-Cell Responses in Allogeneic Hematopoietic Stem Cell Recipients following Two Doses of BNT162b2 mRNA Vaccine

Abstract: Background: At variance to humoral responses, cellular immunity after anti-SARS-CoV-2 vaccines has been poorly explored in recipients of allogeneic hematopoietic stem-cell transplantation (Allo-HSCT), especially within the first post-transplant years where immunosuppression is more profound and harmful. Methods: SARS-CoV-2 Spike protein-specific T-cell responses were explored after two doses of BNT162b2 mRNA vaccine in 45 Allo-HSCT recipients with a median time from transplant of less than 2 years by using INF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“… 13 But Clemenceau et al regularly found T-cell responsiveness in the absence of serologic response. 71 Others have shown that vaccine-induced SARS-Cov-2 S antibody levels in transplant patients and other patients with hematological malignancies are lower than those of healthy volunteers. 5 , 6 , 23 Vice-versa, emerging data suggest that thresholds levels of S- antibodies correlate well with protection.…”
Section: Discussionmentioning
confidence: 99%
“… 13 But Clemenceau et al regularly found T-cell responsiveness in the absence of serologic response. 71 Others have shown that vaccine-induced SARS-Cov-2 S antibody levels in transplant patients and other patients with hematological malignancies are lower than those of healthy volunteers. 5 , 6 , 23 Vice-versa, emerging data suggest that thresholds levels of S- antibodies correlate well with protection.…”
Section: Discussionmentioning
confidence: 99%
“…ǂ variable definition of severe disease, *variable follow-up time. Author, site(s) Diagnosis period # HSCT recipients: auto/allo/CAR-T Age, years – median (range) Time since HSCT or CAR-T – median (range) % asymptomatic % hospitalized % required supplemental O2 % required ICU care % require mechanical ventilation % severe COVID ǂ % COVID-specific mortality* % overall mortality* % mortality (by time from diagnosis) Altuntas, Republic of Turkey (Ministry of Health database) 3/11/20–5/29/20 32: 20/12/0 56.5 [ [17] , [18] , [19] ] 100 22 16 22 16 Coll, Spain (national)*not all lab confirmed on or before 7/13/20 113: 42/71/0 Auto:60 [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ] 18 months [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ...…”
Section: Morbidity and Mortality In Hsct Recipientsmentioning
confidence: 99%
“…Vaccine efficacy in HSCT recipients: While highly immunogenic in the populations included in the large-scale studies that led to vaccine licensing, at least against the original outbreak strain of SARS-CoV-2, numerous, mostly single-center immunogenicity studies have demonstrated decreased, but highly variable, in vitro immune response in HSCT recipients to a 2- or 3-dose mRNA vaccine series as measured by neutralizing antibody and/or T-cell response [ 12 , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ]. Not surprisingly, recency of HSCT, immunosuppressive therapy, lymphopenia, active malignancy and GVHD have all been demonstrated to be associated with dampened immune response.…”
Section: Vaccination In Hsct Recipientsmentioning
confidence: 99%
“…Results of cellular vaccination responses in allo-HCT recipients are heterogeneous and not widely available. Methods used were ELISpot and/or intracellular cytokine staining and reported response rates have ranged from < 30% 9,22 to high response rates of > 75% 20,21 . We used an easy to perform, standardized and validated assay with high speci city of 96.3-100% and sensitivity of 75.4-86.9% to detect past infection 23 .…”
Section: Discussionmentioning
confidence: 99%